Coaching as a tool for people development in organizational context: professionals identify demands and outcomes - Fontes, A.; Dello Russo, S. (IX Simpósio de Comportamento Organizacional, 2018)
Coaching industry has an established place when we analyze it worldwide. Although in Portugal is a more recent practice, with some critics particularly related to the difficulty of explaining its effectiveness. Our main objective with descriptive study was to better understand the coaching context in Portugal, seen through the lens of the professionals. A survey for coaching practitioners was distributed online with a final sample of 187 coaches. This survey included 22 questions grouped in six different sections: demographics, experience and training of the coach, coaching practices and theoretical approach, clients’ characteristics and questions brought, obtained results and future trends. When analyzing the objectives brought by the coachee, coaching services are required mainly for leadership and decision purposes that appears outstandingly in the first position of the ranking while support and cooperation appears in the bottom. Regarding the consequences of coaching, coaches report most impact on hope/optimism and self- awareness as main positive consequences. Focus on objectives, motivation for work, resilience, self-efficacy and commitment with the company follow the ranking order. In the last positions we found the ability to deal with change and leadership competencies. Important to note that leadership competencies’ development s is the most demanded area in coaching services, but the improvement of leadership appears as the last positive consequence of coaching. This divergence definitely lead us to the discussion about the mediating mechanisms responsible for coaching effectiveness. Also, some negative consequences of coaching are reported, such as coachee’s goals being modified without their permission or having to deal with in-depth problems that could not be handled with in the coaching sessions. Equally these finding can open the discussion about the competencies that a coach should have in order to better contribute for the effectiveness of this practice. With this picture of the portuguese context regarding coaching practices, we intend to highlight the need for more scientific research about the ingredients, the theory – driven methodologies and mediating mechanisms of coaching efficacy. We intend to contribute therefore for the coaching development as a replicable a standardized tool for people development, especially in the corporate context.